Execute of Chemotherapy Medicines on Cancer Patients (Asian Journal of Pharmaceutics (AJP), 2023)
Chemotherapy still has several side effects that might lower a patient’s quality of life, despite improvements inchemotherapeutic techniques and drugs. This review’s objective is to identify and characterize the adverse effectsthat are unique to chemotherapy. This essay provides a thorough analysis of the major side effects that have animpact on chemotherapy patients’ overall health. Cancer patients also encounter a wide range of symptoms, bothphysical and psychological. These symptoms can be a result of the sickness or the medication and can vary infrequency, severity, and level of distress.